2014
DOI: 10.1590/s1415-47572014000200011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of holoprosencephaly in South America

Abstract: Holoprosencephaly (HPE) is a spectrum of brain and facial malformations primarily reflecting genetic factors, such as chromosomal abnormalities and gene mutations. Here, we present a clinical and molecular analysis of 195 probands with HPE or microforms; approximately 72% of the patients were derived from the Latin American Collaborative Study of Congenital Malformations (ECLAMC), and 82% of the patients were newborns. Alobar HPE was the predominant brain defect in almost all facial defect categories, except f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
1
4
0
2
Order By: Relevance
“…The agenesis of the premaxillary bone in some diseases 48 , 49 makes its existence and autonomy obvious, because the bone posterior to the premaxillary-maxillary suture, the maxillary bone, is present and functional.…”
Section: Discussionmentioning
confidence: 99%
“…The agenesis of the premaxillary bone in some diseases 48 , 49 makes its existence and autonomy obvious, because the bone posterior to the premaxillary-maxillary suture, the maxillary bone, is present and functional.…”
Section: Discussionmentioning
confidence: 99%
“…Double strands of the coding regions and exon-intron borders of SHH, ZIC2, SIX3, and TGIF1 genes were submitted to Sanger sequencing. Amplification protocols of these regions and primers were described in Savastano et al [2014]. Amplicons were visualized in 1% agarose gel and further purified by GFX PCR DNA and Gel Band Purification kit (Ge Healthcare, UK), according to the manufacturer's instructions.…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…Additional evidence coming from studies on the chick embryo have shown that alcohol produces the suppression of Wnt and Shh signals, which thereby alter the migration, expansion and survival of the NCCs (Flentke & Smith, ). In addition, scientific evidence has shown that exposure to high levels of maternal ethanol and to high blood sugar levels during pregnancy (gestational diabetes) can also lead to a holoprosencephalic phenotype in humans (Barr et al, ; Savastano et al, ). Recently, a correlation between the increased risk of neuroblastoma and parental alcohol use has been proposed, thus highlighting the importance of a healthy lifestyle during pregnancy (Müller‐Schulte, Kurlemann, Harder, & Edition, ).…”
Section: Chemical Agentsmentioning
confidence: 99%